Morphological and Chemical Analysis of Various Disposable Acupuncture Needles Used in South Korea - Dong Yong Park; JiYoon Ahn; Hyeon Jeong Park; Doo Suk Lee; Dae-Hyun Jo; Jonghoon Kim; Choulmin Kim; Heebum Chung; Ji Hye Hwang (Korean Pharmacopuncture Institute, 2022)
Objectives: The Korean Industrial Standard (KS) for sterile acupuncture needles was established in 2009 based on research on the quality control of acupuncture needles. We aimed to determine the quality of acupuncture needles available in South Korea in 2021 by examining their surface condition and chemical composition using field-emission scanning electron microscopy (FE-SEM) and energy-dispersive X-ray spectroscopy (EDS).Methods: In South Korea, there are 23 brands of acupuncture needles, and we examined 10-15 needles from each brand, resulting in a total of 285 needles. The microstructures of the needles were assessed by SEM. Using SEM images, we evaluated the acupuncture needle tips for the following defects/aspects: scratches, lumps, detached coating, bent tip, and tip sharpness. EDS was used to determine the chemical composition of the selected acupuncture needles.Results: Overall, 88.4% of 285 needles were found to have at least one type of abnormality. The most frequently observed abnormalities were scratches and dents on the surface (68.1%), followed by detached coating (63.2%), and lumps (61.8%); blunt tips were observed in about 24% of them. Of 252 needles with at least one defect, 86.9% had two or more types of defects. The ratio of the number of needles with any defect to that of needles without any defect varied among brands, ranging from 50% to 100%. Regarding foreign materials, higher proportions of Si and O were observed on the needles, indicating incomplete or detached silicone coating.Conclusion: The quality of acupuncture needles varied among brands, suggesting that further improvements can be made through various inspection methods.